Correlation between Mean Platelet Volume, Fibrinogen and D-dimer with NIHSS Score - Nasution, Putra Fajar; Irina, Rr Sinta; Lubis, Bastian (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2024)
Introduction: Stroke is a clinical syndrome that develops rapidly due to focal or global brain disorders with symptoms last for 24 hours and potentially cause death. Due to the consideration that this Mean Platelet Volume (MPV) marker is not invasive, easy to do and is in line with the pathogenesis of stroke, researchers are interested in carrying out this research. And hopefully this research can provide information for the world of education and health about changes in MPV, fibrinogen and D-dimer in ischemic stroke patients. So it can be taken as consideration in the early management of ischemic stroke patients. Subject and Methods: This research was an observational study with a cross-sectional design at Haji Adam Malik General Hospital from October to November 2023. The research subjects were stroke patients who were treated in emergency room and met inclusion criteria. This research was to study about correlation of MPV, fibrinogen, and D-dimer with NIHSS scores of ischemic stroke patients. The method used in this research is the Pearson correlation test where data was normally distributed. All statistical tests with a p value 0.05 were considered significant. Results: The mean MPV was 10.4 1.6, while the mean NIHSS value was 19.9 8.7, and there was a statistically significant correlation between the MPV value and the NIHSS score (p0.05). The mean fibrinogen was 421.9 109.3, while mean NIHSS value was 19.9 8.7, and there was a statistically significant correlation between fibrinogen values and NIHSS scores (p0.001). The mean D-Dimer was 8.0 11.3, while the mean NIHSS value was 19.9 8.7, and showed a statistically significant correlation between D-Dimer value and NIHSS score (p0.05). The r value of MPV, fibrinogen, and D-dimer on NIHSS score was 0.494; 0.495; and 0.504. The regression coefficient for MPV variable is 0.093, therefore MPV variable influence on NIHSS variable is positive.Conclusion: There is a strong correlation between D-dimer and the NIHSS score, and a moderate correlation between MPV and fibrinogen with NIHSS score.